PENGARUH METODE TEMUAN TERBIMBING TERHADAP KEMAMPUAN SAINS ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK - Ika Dwi Fatmi; Zulminiati Zulminiati (UNIVERSITAS PGRI MADIUN, 2022)
The istudy iwas iconducted ito idetermine iwhether ithere iis ian ieffect iof iusing ithe iguided ifinding imethod ion ithe iscience iability iof ichildren iaged i5-6 iyears iin iKindergarten. iThe imethod iused iin ithis istudy iis ia iquantitative iQuasi iexperimental idesign i(quasi-experimental). iSampling iin ithis istudy iused ia ipurposive isampling itechnique iwhich iconsisted iof itwo igroups, inamely ithe iexperimental iclass iand ithe icontrol iclass. iData icollection itechniques iin ithe iform iof igiving ipretest iand iposttest ito idetermine ithe iability ibefore iand iafter ibeing igiven idifferent itreatment iin ieach igroup. iAnalysis iof ithe idata iused ito isee ithe ieffect iof ithe imethod iusing ithe iPrerequisite iTest, inamely ithe idata inormality itest iand ithe idata ihomogeneity itest iwith ia isignificance ilevel iof i0.05 iand ithe it-test, iwhich iis ia iparametric istatistical itest iusing ia ipaired isample itest ibecause ithe idata iis ipaired. iThe iresults iof idata ianalysis ishowed ithat ithere iwere idifferences iin ithe iaverage ivalue iof ithe iscience iability iof ichildren iaged i5-6 iyears ibefore iand iafter ibeing igiven itreatment, ithe iSig ivalue iwas iobtained. i(2-tailed) i0.000 i< i0.05. iThus, iit ican ibe iconcluded ithat ithere iis ia isignificant ieffect ion ithe iuse iof ithe iguided ifinding imethod ion ithe iscience iability iof ichildren iaged i5-6 iyears iin iKindergarten.